Ternary self-assemblies in water: forming a pentanuclear ReLn4 assembly by association of binuclear lanthanide binding pockets with fac-Re(CO)3(dinicotinate)2Cl. - Hill, L; Blackburn, O; Jones, M; Tropiano, M; Sørensen, T; Faulkner, S (2013)
The self-assembly of higher order structures in water is realised by using the association of 1,3-biscarboxylates to binuclear meta-xylyl bridged DO3A complexes. Two dinicotinate binding sites are placed at a right-angle in a rhenium complex, which is shown to form a 1 : 2 complex with α,α'-bis(Eu·DO3A)-5-amino-m-xylene.